2021
DOI: 10.1002/ehf2.13599
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy defibrillators in patients with permanent atrial fibrillation

Abstract: Aims There are conflicting data on the benefit of cardiac resynchronization therapy (CRT) in heart failure (HF) patients with permanent atrial fibrillation (AF). We aimed to compare patient outcomes according to the presence or absence of permanent AF at device implantation. Methods and resultsWe retrospectively analysed remote monitoring data from 1141 CRT defibrillators. Propensity score with inverse-probability weighting method was used to balance AF and sinus rhythm (SR) groups. Analysis endpoints included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(38 reference statements)
1
2
1
Order By: Relevance
“…By contrast, in our study the effectiveness of CRT in ARNi and SGLT2i group was consistent regardless HF etiology, but especially in ICM patients that least responded to the CRT. Interestingly, the other well-known negatively predictors of CRT clinical outcomes (such as atrial fibrillation, RBBB, biventricular pacing) were confirmed in our analysis [30][31][32] .…”
Section: Impact Of Arni and Sglt2i In Clinical And Echocardiographic ...supporting
confidence: 77%
“…By contrast, in our study the effectiveness of CRT in ARNi and SGLT2i group was consistent regardless HF etiology, but especially in ICM patients that least responded to the CRT. Interestingly, the other well-known negatively predictors of CRT clinical outcomes (such as atrial fibrillation, RBBB, biventricular pacing) were confirmed in our analysis [30][31][32] .…”
Section: Impact Of Arni and Sglt2i In Clinical And Echocardiographic ...supporting
confidence: 77%
“…In our study, only 5.2% patients initially eligible for CRT implantation had LVEF improvement to ≥50% with SAC/VAL treatment alone for 12 months, suggesting the important role of electrical dyssynchrony in a substantial portion of patients. Besides, the previous studies demonstrated that permanent atrial fibrillation may influence biventricular pacing percentage and reverse cardiac remodelling in HFrEF patients receiving CRT implantation 23,24 . Nevertheless, this study showed that the association between the effects of SAC/VAL in reverse cardiac remodelling and permanent atrial fibrillation were insignificant regardless of the QRS durations in Groups 1 and 2.…”
Section: Resultscontrasting
confidence: 50%
“…Besides, the previous studies demonstrated that permanent atrial fibrillation may influence biventricular pacing percentage and reverse cardiac remodelling in HFrEF patients receiving CRT implantation. 23,24 Nevertheless, this study showed that the association between the effects of SAC/VAL in reverse cardiac remodelling and permanent atrial fibrillation were insignificant regardless of the QRS durations in Groups 1 and 2. Therefore, more studies were warranted to clarify the association of SAC/VAL effects in reverse cardiac remodelling and permanent atrial fibrillation in HFrEF patients with different QRS durations.…”
Section: Discussionmentioning
confidence: 55%
“…However, several studies revealed a necessity for high bi-ventricular (BiV) pacing rates to achieve these beneficial effects [8][9][10][11]. In clinical practice, reaching high BiV pacing rates might be challenging due to rapid intrinsic atrioventricular conduction during atrial tachycardia or atrial fibrillation [12][13][14]. Furthermore, premature ventricular contractions (PVC) can lead to a significant reduction in BiV pacing rates [15,16].…”
Section: Introductionmentioning
confidence: 99%